A Simulation-Based Optimization Framework for Improving Customer Waiting Time During Vehicle Inspection Process - Khibtiyah Ilyas; Norazura Ahmad; Norhaslinda Zainal Abidin (International Journal of Supply Chain Management, 2019)
Issue of long customer waiting time is a common issue at service industry. A Vehicle Inspection Centre (VIC) is one of the service industries that faces this issue and has a significant impact on quality of service. The management of VIC has been struggling in applying alternative solutions to reduce the customer waiting time, but the long customer waiting time still occurs. Therefore, the management requires an appropriate tool that contributes to improve customer waiting time problem and indirectly improving quality of service. To assist the management, a simulation-based optimization framework is presented in this paper to mitigate the issue of long customer waiting time. The preliminary result of the implementation of the framework on customer waiting time at VIC is also presented in this paper.